Developing perspectives in Mamluk history : essays in honor of Amalia Levanoni - Ben-Bassat, Yuval.; Levanoni, Amalia. (Islamic History and Civilization, 2017)
The present volume contains seventeen essays on the Mamluk Sultanate, an Islamic Empire of slaves whose capital was in Cairo between the 13th and the 16th centuries, written by leading historians of this period. It discusses topics as varied as social and cultural issues, women in Mamluk society, literary and poetical genres, the politics of material culture, and regional and local politics. The volume presents state of the art scholarship in the field of Mamluk studies as well as an in-depth review of recent developments. Mamluk studies have expanded considerably in recent years and today interests hundreds of active researchers worldwide who write in numerous languages and constitute a vivid and strong community of researchers, some of whose best research is presented in this volume. With contributions by Reuven Amitai; Frédéric Bauden; Yuval Ben-Bassat; Joseph Drory; Élise Franssen; Yehoshua Frenkel; Li Guo; Daisuke Igarashi; Yaacov Lev; Bernadette Martel-Thoumian; Carl Petry; Warren Schultz; Boaz Shoshan; Hana Taragan; Bethany J. Walker; Michael Winter; Koby Yosef; Limor Yungman.